2017
DOI: 10.2903/j.efsa.2017.4676
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of microorganism DSM 11798 as a technological additive for all avian species

Abstract: Biomin® BBSH 797 is the trade name for a feed additive containing viable cells of an unnamed bacterium (DSM 11798). The EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) produced an opinion on the safety and efficacy of this additive when used with pigs concluding that the additive itself did not raise any safety concern. It was confirmed that the additive could reduce the trichothecene, deoxynivalenol (DON), producing the less toxic de-epoxy metabolite. The applicant is now seeki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…It was the first microorganism applied as a mycotoxin deactivating additive in feed. Regarding the microorganism DSM 11798 Genus nov. species nov. (BBSH 797) product, EFSA (European Food Safety Authority) delivered a positive opinion on its safety for the target animals (pigs and avian species), consumer, user and the environment, when used under the proposed conditions [ 47 , 48 ]. The appropriate implementing regulations were established in 2016 and 2017 [ 49 , 50 ].…”
Section: Post-harvest Biological Controlmentioning
confidence: 99%
“…It was the first microorganism applied as a mycotoxin deactivating additive in feed. Regarding the microorganism DSM 11798 Genus nov. species nov. (BBSH 797) product, EFSA (European Food Safety Authority) delivered a positive opinion on its safety for the target animals (pigs and avian species), consumer, user and the environment, when used under the proposed conditions [ 47 , 48 ]. The appropriate implementing regulations were established in 2016 and 2017 [ 49 , 50 ].…”
Section: Post-harvest Biological Controlmentioning
confidence: 99%
“…Commercial products, such as Biomin ® BBSH 797 containing biotransform agents, have also been developed and patented as feed additives (EFSA, 2005). Biomin ® BBSH 797 is the first microorganism authorized by the European Food Safety Authority that converts trichothecenes into less toxic metabolites for poultry and swine diets (Rychen et al., 2017). This microorganism can convert DON into DOM‐1.…”
Section: Degradation Of Don By Microorganismsmentioning
confidence: 99%
“…Farzaneh et al obtained a promising A. flavus R5 antagonist strain B. subtilis UTBSP1, which can reduce the growth of A. flavus R5 and aflatoxins accumulation(Farzaneh et al, 2016).Additives et al displayed the strain Eubacterium BBSH 797, isolated from bovine rumen fluid, can transform the deoxynivalenol (DON) to nontoxic metabolite trichothecenes due to its epoxidase(Additives et al, 2017). Li et al found that B. velezensis from the surface of a healthy race significantly controls A. flavus contamination(Li et al 2022).…”
mentioning
confidence: 99%